OPTIMALISASI KINERJA KARYAWAN MELALUI KESEHATAN DAN KESELAMATAN KERJA DI RS ARIA KAMUNING - Permana, Diosaka Zahran Agung (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
This research aims to explain the influence of health and safety partially on employee performance, to explain the influence of occupational health and safety simultaneously on employee performance. Based on the results of the analysis, it shows that occupational health and safety have a significant effect on the performance of Aria Kamuning Hospital employees. The sampling technique is using saturated sampling. Saturated sampling is a technique for determining the sample if all members of the population are used as samples. The number of samples used in this research was 98 respondents who were employees of Aria Kamuning Hospital. The data analysis technique in this research was carried out using the testing stage of multiple linear regression analysis and classical assumption regression analysis. The research results show that the work environment influences employee performance. Work Safety Variable (X1) t_calculated value is 0.437 with a probability of 0.663. Because the probability value (sig) t < 5% (0.663 > 0.05), partially the Work Safety variable (X1) has a positive and significant effect on the Employee Performance variable (Y). The Occupational Health variable (X2) has a calculated t_value of - 0.651 with a probability of 0.517. Because the probability value (sig) t < 5% (0.517 > 0.05) then partially the Occupational Health variable (X2) has a significant positive effect on the Employee Performance variable (Y). From table 3 above it can be seen that the F_count value (0.289) is greater from the F_table value (2.70), while the significance value obtained is 0.003 < 0.05. F table is obtained by df1 = k-1 = 3-1 = 2 and df2 = n-k = 87-3 = 84, then the F_table value is 2.70. So it can be concluded that simultaneously the variables of occupational safety and occupational health affect employee performance.